Pengaruh Literasi Akuntansi, Literasi Perpajakan dan Literasi Teknologi Informasi Terhadap Minat Berkarir Menjadi Akuntan Publik dengan Kemampuan Berpikir Kritis Sebagai Pemoderasi - Tambun, Sihar; Setyowati, Riska Dewi; Julito, Kiko Armenita (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to prove the influence of accounting literacy, tax literacy, and information technology literacy on career interest as a public accountant. Then prove the moderating impact of critical thinking on the influence of accounting literacy, tax literacy, and information technology literacy on career interest as a public accountant. The statistical analysis method used is multivariate analysis with structural equation modeling, to prove the direct effect and moderating effect hypotheses. The analysis uses Smart PLS 4 software. The research sample is 151 accounting students with the determination of the number of samples using the Hair method. The results of the study prove that directly accounting literacy, information technology literacy, and critical thinking skills have a positive impact on career interest as a public accountant. Meanwhile, critical thinking skills are unable to strengthen the influence of accounting literacy, tax literacy, and information technology literacy on career interest as a public accountant. The implication is that critical thinking skills cannot synergize with accounting literacy, tax literacy and information technology literacy to increase interest in pursuing a career as a public accountant.